Knowledge and Attitudes of Eligible Women With Behavioral Examination Inspection Acetic Acid (VIA) - Fitria Zuhriyatun; Septerina P W; Fajaria N A (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
This is an analytical research to determine Correlation between Knowledge and Attitudes of woman in childbearing age (WCA) on Visual Inspection Acetic Acid (VIA) with Behavior to Perform the VIA Inspection in the area of Health Center I Kebumen in 2013 .This study uses a cross-sectional approach with 93 WCA sample who are chosen using cluster sampling technique and simple random sampling. Questionnaire which its reliability and validity have already tested is used to collect the data. Then we analyze them using Chi Square formula. Research results shows that the respondents have knowledge about the VIA with the category of good ( 10.8 % ), enough ( 79.6 % ), and doubt ( 51.6 % ). There is a significant correlation between these two variable, with the acquisition of Chi Square correlation coefficient of 9.011 and a P - Value of 0.011. Significant relationship exists between respondents' attitudes toward VIA with behavior to be examine, with the acquisition of Chi Square correlation coefficient of 24.841 and a P - Value of 0.000.